Effects of Arteriovenous Fistula on Blood Pressure in Patients With End‐Stage Renal Disease: A Systematic Meta‐Analysis - Sean S. Scholz; Davor Vukadinović; Lucas Lauder; Sebastian Ewen; Christian Ukena; Raymond R. Townsend; Stefan Wagenpfeil; Michael Böhm; Felix Mahfoud (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Central arteriovenous fistula (AVF) creation is under investigation for treatment of severe hypertension. We evaluated the effects of AVF for initiation of hemodialysis on systolic, diastolic, and mean arterial blood pressure in patients with end‐stage renal disease. Methods and Results Data search included PubMed, Web of Science, and the Cochrane Library. A systematic review and meta‐analysis of peer‐reviewed studies reporting the effects of the creation/ligation of an AVF on blood pressure in patients with end‐stage renal disease was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analysis), PRISMA‐P (PRISMA for systematic review protocols), and ROBINS‐I (Risk of Bias in Non‐Randomized Studies) criteria by the Cochrane Bias Methods Group. All studies in which the results could have been biased by hemodialysis were excluded. A total of 14 trials including 412 patients with end‐stage renal disease (AVF creation, n=185; AVF ligation, n=227) fulfilled the criteria and were subsequently analyzed. Average blood pressure in patients with no/closed AVF was 140.5/77.6 mm Hg with a mean arterial blood pressure of 96.1 mm Hg. Following creation of AVF, systolic blood pressure significantly decreased by 8.7 mm Hg (P<0.001), diastolic blood pressure by 5.9 mm Hg (P<0.001), and mean arterial blood pressure by 6.6 mm Hg (P=0.02), whereas after ligation systolic blood pressure increased by 5.2 mm Hg (P=0.07), diastolic blood pressure by 3.8 mm Hg (P=0.02), and mean arterial blood pressure by 3.7 mm Hg (P=0.07) during short‐ to long‐term follow‐up. Conclusions Creation of AVF significantly decreases blood pressure in patients with end‐stage renal disease, whereas blood pressure tends to increase after ligation. These findings illustrate the hemodynamic consequences of AVF which are under investigation for severe hypertension.